THE SIMULATION AND PARAMETRIZATION OF THE LATERAL DISTRIBUTION FUNCTION IN EAS AT ULTRA HIGH ENERGIES - Raham, Abbas Rahi; Merza, Qays Kamal (PT. Antis International Publisher, 2024)
To characterize the features of EASs, this study used the AIRES simulation tool (Version 19.04.0) to estimate the lateral distribution function (LDF) at very high energies of different types of cosmic ray particles. An array of zenith angles spanning from 1018 to 1020 eV was used for the proton and iron primary simulations. The EASs's LDF curves are fitted with new coefficients for various primary particles and zenith angles using a polynomial fit, and these coefficients are applicable to the energy range described before. The findings of the simulation were compared with actual data from the Yakutsk EAS array, which showed decent agreement for proton and iron at 1019 eV for angled showers at θ=10ˢ.